2021
DOI: 10.1016/j.celrep.2021.109673
|View full text |Cite|
|
Sign up to set email alerts
|

Viral targeting of glioblastoma stem cells with patient-specific genetic and post-translational p53 deregulations

Abstract: Highlights d Human GSCs mount heterogeneous patient-specific innate responses to parvoviruses d Parvovirus infection induces DDR and bystander damage in GSC-derived brain tumors d p53-Ser15 phosphorylation enhances parvovirus genome replication in cancer cells d GSCs with p53 gain-of-function mutations are main targets of parvovirus infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 119 publications
(157 reference statements)
0
13
0
Order By: Relevance
“…Some reports suggest that the ONYX-15 p53 gene therapy actually relies on deregulated p53 signalling and works best in mutp53 cells [ 145 ], although others demonstrated enhanced oncolytic activity of ONYX-15 in WTp53 cells [ 146 ] or activity that was independent on p53 status [ 147 , 148 ]. More recently, parvovirus targeting of glioblastoma stem cells with a cytotoxic protein NS1 showed that this virus is more effective in mutp53 cells [ 149 ]. These studies likely suggest disease/cell specificity and raise the question on how p53 is involved in viral infection, viral replication, and which patient would benefit most from such therapies.…”
Section: Strategies That Exploit Mutant P53 Expressionmentioning
confidence: 99%
“…Some reports suggest that the ONYX-15 p53 gene therapy actually relies on deregulated p53 signalling and works best in mutp53 cells [ 145 ], although others demonstrated enhanced oncolytic activity of ONYX-15 in WTp53 cells [ 146 ] or activity that was independent on p53 status [ 147 , 148 ]. More recently, parvovirus targeting of glioblastoma stem cells with a cytotoxic protein NS1 showed that this virus is more effective in mutp53 cells [ 149 ]. These studies likely suggest disease/cell specificity and raise the question on how p53 is involved in viral infection, viral replication, and which patient would benefit most from such therapies.…”
Section: Strategies That Exploit Mutant P53 Expressionmentioning
confidence: 99%
“…The origin of the A9 ouabr11 mouse cell line, the human-transformed NB324K fibroblast and U373MG glioblastoma cells, and the respective media and culture conditions have been previously described (Gil-Ranedo et al, 2021 ). MVMp and chimeric viruses were produced by electroporation of NB324K cells with the respective infectious molecular clones following a previously described method (Lombardo et al, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, large viral stocks were prepared by infecting NB324K at a multiplicity of infection (MOI) of 10 −3 infectious units/cell and culturing for 5–7 days until the cell monolayers showed a moderate cytopathic effect. The total virus was purified by sucrose cushions and cesium chloride equilibrium centrifugation, and DNA-filled virions were pooled, dialyzed against PBS, and kept at −70°C in aliquots following previously described procedures (Lombardo et al, 2002 ; Gil-Ranedo et al, 2021 ). Viral stocks were routinely checked for genetic stability in the VP sequence surrounding the inserted peptides to avoid the possible selection of mutants overcoming assembly restrictions (Grueso et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Parvovirinae have an important potential in oncolytic therapy, AAVs are a major platform in gene therapy. H‐1PV and MVM are known to induce lysis of transformed cells and to activate anticancer immune responses (Abschuetz et al, 2006 ; Geletneky et al, 2017 ; Gil‐Ranedo et al, 2021 ; Grekova et al, 2012 ; Hartley et al, 2020 ; Marchini et al, 2015 ). The role of CPV in inducing an antitumor immune response in different tumor models has been discussed (Arora et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%